Pengaruh Pemberian Pendidikan Kesehatan Dengan Leaflet Terhadap Tingkat Pencegahan Keputihan Pada Remaja Putri Di Pondok Pesantren Al-Jamil Purwokerto - Septiyani Nur Pujiati; Siti Haniyah; Linda Yanti (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Teenagers are less aware of the hygiene of their genital organs. This can cause problems in reproductive health, one of which is vaginal discharge. Fluor albus or commonly known as vaginal discharge is a term for discharge from female genitalia that is not blood. This problem can be prevented by providing health education knowledge. This study aims to determine the effect of providing health education with leaflets on the level of prevention of vaginal discharge in adolescent girls at Pondok Pesantren Al-Jamil Purwokerto. This research is a quantitative study with a Pre-experiment approach and One Group Pretest-Postest Design. The sampling technique used was purposive sampling and the respondents obtained were 25 people. Statistical analysis using the Wilcoxon Signed Rank Test. The results of this study prove that there is a significant effect between the provision of health education with leaflets on the level of vaginal discharge prevention in adolescent girls with a mean difference of 6.92 and 9.76. Wilcoxon p-value analysis test results (p=0.000). There is an effect of providing health education knowledge with leaflets on the level of prevention of vaginal discharge in adolescent girls at PP Al-Jamil Purwokerto.